A walk to remember (Warner Bros., 2013)
Jamie is a preacher's daughter whose self-confidence doesn't depend on the opinions of others. Landon is skating through high school on looks and bravado. But when events thrust him into Jamie's world, he begins an unexpected journey he will never forget. The remarkable steps to a life changed involve trust, hope, goals, faith and unconditional love.